2017
DOI: 10.1016/j.kjms.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Microdissection testicular sperm extraction (micro‐TESE): Predictive value of preoperative hormonal levels and pathology in non‐obstructive azoospermia

Abstract: The aim of this study was to evaluate the predictive value of preoperative hormonal levels and pathology, as well as the outcome of microsurgical testicular sperm extraction in patients with non-obstructive azoospermia (NOA), presenting to our clinic for treatment of infertility. The records of 145 men with NOA who underwent microdissection testicular sperm extraction (micro-TESE) between March 2013 and November 2016 were studied. The patient's age, testicular volume, hormonal profile for follicle-stimulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 29 publications
8
46
1
Order By: Relevance
“…The rate of sperm retrieval from hypospermatogenetic testis in our study is lower than those indicated in literature. [15,16] This is because the other factors (testicular volume, hormone profile, etc.) related to the testes were lower in these patients, and they were subject to recurrent mTESE operations.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of sperm retrieval from hypospermatogenetic testis in our study is lower than those indicated in literature. [15,16] This is because the other factors (testicular volume, hormone profile, etc.) related to the testes were lower in these patients, and they were subject to recurrent mTESE operations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they obtained cutoff points of 400 ng/mL for total testosterone and 11 pg/mL for free testosterone with predictive accuracies of 37.7% and 35.5%, respectively. By contrast, the majority of studies analyzed both total and free levels of serum testosterone in the aforementioned groups of patients did not corroborate this statistically significant difference between the groups and therefore have concluded that serum testosterone lacks any value in predicting sperm retrieval rate by TESE operation [14,18,19,23,27,30]. Moreover, in reports which proposed testosterone as a predictive biomarker, serum testosterone level either acts as a part of a multivariate model or lacks sufficient sensitivity and specificity required for clinical application.…”
Section: Testosteronementioning
confidence: 95%
“…Similarly, Bonarriba et al [25] have introduced the cutoff point of 12.2 mIU/mL for serum FSH with sensitivity and specificity of 71% and 75%, respectively. Nevertheless, it is generally accepted that the serum FSH has a poor value for predicting the existence of sperm in the testes [27,28,30]. Indeed, cases with even serum FSH > 90 mIU/mL but positive TESE outcomes have been observed in previous studies [21].…”
Section: Follicle-stimulating Hormonementioning
confidence: 99%
See 1 more Smart Citation
“…Another example in which futility was determined involved a male partner who lacked viable spermatozoa. A determination of futility is also inappropriate because multiple studies indicate that treatment chances can be as high as 25% and 36% [66][67][68]. Another example involved a couple who underwent numerous IVF cycles without adequate egg production, fertilization, or embryo development.…”
Section: There Is a Need To Diagnose Sterility Prospectivelymentioning
confidence: 99%